Application Model Problem Based Learning To Improve Learning Outcomes Class II Elementary School - Nur Qomalasari, Elsa; Nurkholis, Nurkholis; Rinto, Rinto (Jurnal Edusci, 2023)
This Research aims for increasing of learn result at second grade SDN 2 Dukuhmaja which has eleven students on fractions material with teacher’s effort on planning and doing teaching-learning process using Problem Based Learning model. It becaused of class condition with the problems (2) learn result of math was low specifically in fraction material with classical mastery 45,4 %, (2) low of using variation on method and model in teaching, (3) limited for availability of media, tools and infrastructure which support learning process. Based on the research obtains learn result from student’s comprehension in first cycle classical mastery get 63,6% with seven students completed and four students uncompleted. In second cycle, classical mastery reaches 100 % with elven students completed. As for measuring teacher’s skills for planning in first cycle get 3.5 score and 3,8 score in second cycle with really good category. While for doing teaching learning process in first cycle get 3 score and second cycle get 3,5 with really good category. This research projecting in order that implementation of Problem Based Learning model in classroom action research should pay attention in each step and increase so many references for used in learning.